Elucidating the structure-dependent selectivity of CuZn towards methane and ethanol in CO2 electroreduction using tailored Cu/ZnO precatalysts. Issue 43 (21st October 2021) - Varandili, Seyedeh Behnaz; Stoian, Dragos; Vavra, Jan; Rossi, Kevin; Pankhurst, James R.; Guntern, Yannick T.; López, Núria; Buonsanti, Raffaella
Abstract : A higher degree of surface alloying and Zn concentration boosts the selectivity towards ethanol of CuZn catalysts in CO2 electroreduction. Abstract : Understanding the catalyst compositional and structural features that control selectivity is of uttermost importance to target desired products in chemical reactions. In this joint experimental–computational work, we leverage tailored Cu/ZnO precatalysts as a material platform to identify the intrinsic features of methane-producing and ethanol-producing CuZn catalysts in the electrochemical CO2 reduction reaction (CO2 RR). Specifically, we find that Cu@ZnO nanocrystals, where a central Cu domain is decorated with ZnO domains, and ZnO@Cu nanocrystals, where a central ZnO domain is decorated with Cu domains, evolve into Cu@CuZn core@shell catalysts that are selective for methane (∼52%) and ethanol (∼39%), respectively. Operando X-ray absorption spectroscopy and various microscopy methods evidence that a higher degree of surface alloying along with a higher concentration of metallic Zn improve the ethanol selectivity. Density functional theory explains that the combination of electronic and tandem effects accounts for such selectivity. These findings mark a step ahead towards understanding structure–property relationships in bimetallic catalysts for the CO2 RR and their rational tuning to increase selectivity towards target products, especially alcohols.